Tumor-derived exosomal HMGB1 fosters hepatocellular carcinoma immune evasion by promoting TIM-1+ regulatory B cell expansion - Ye, Linsen; Zhang, Qi; Cheng, Yusheng; Chen, Xiaolong; Wang, Guoying; Shi, Mengchen; Zhang, Tong; Cao, Yingjiao; Pan, Hang; Zhang, Liting; Wang, Genshu; Deng, Yinan; et al. (Journal for immunotherapy of cancer, 2018)
Regulatory B (Breg) cells represent one of the B cell subsets that infiltrate solid tumors and exhibit distinct phenotypes in different tumor microenvironments. However, the phenotype, function and clinical relevance of Breg cells in human hepatocellular carcinoma (HCC) are presently unknown. Flow cytometry analyses were performed to determine the levels, phenotypes and functions of TIM-1 Breg cells in samples from 51 patients with HCC. Kaplan-Meier plots for overall survival and disease-free survival were generated using the log-rank test. TIM-1 Breg cells and CD8 T cells were isolated, stimulated and/or cultured in vitro for functional assays. Exosomes and B cells were isolated and cultured in vitro for TIM-1 Breg cell expansion assays. Patients with HCC showed a significantly higher TIM-1 Breg cell infiltration in their tumor tissue compared with the paired peritumoral tissue. The infiltrating TIM-1 Breg cells showed a CD5 CD24 CD27 CD38 phenotype, expressed high levels of the immunosuppressive cytokine IL-10 and exhibited strong suppressive activity against CD8 T cells. B cells activated by tumor-derived exosomes strongly expressed TIM-1 protein and were equipped with suppressive activity against CD8 T cells similar to TIM-1 Breg cells isolated from HCC tumor tissue. Moreover, the accumulation of TIM-1 Breg cells in tumors was associated with advanced disease stage, predicted early recurrence in HCC and reduced HCC patient survival. Exosome-derived HMGB1 activated B cells and promoted TIM-1 Breg cell expansion via the Toll like receptor (TLR) 2/4 and mitogen-activated protein kinase (MAPK) signaling pathways. Our results illuminate a novel mechanism of TIM-1 Breg cell-mediated immune escape in HCC and provide functional evidence for the use of these novel exosomal HMGB1-TLR2/4-MAPK pathways to prevent and to treat this immune tolerance feature of HCC.